Pain Frequency and Health Care Utilization Patterns in Women with Sickle Cell Disease Experiencing Menstruation-Associated Pain Crises - Segbefia, C.; Campbell, J.; Tartaglione, I.; et al. (Journal of Women's Health, 2023)
Background: Pain crises in sickle cell disease (SCD) lead to high rates of health care utilization. Historically, women have reported higher pain burdens than men, with recent studies showing a temporal association between pain crisis and menstruation. However, health care utilization patterns of SCD women with menstruation associated pain crises have not been reported. We studied the frequency, severity, and health care utilization of menstruation-associated pain crises in SCD women. Materials and Methods: A multinational, cross-sectional cohort study of the SCD phenotype was executed using a validated questionnaire and medical chart review from the Consortium for the Advancement of Sickle Cell Research (CASiRe) cohort. Total number of pain crises, emergency room/day hospital visits, and hospitalizations were collected from a subcohort of 178 SCD women within the past 6 months and previous year. Results: Thirty-nine percent of women reported menstruation-associated pain crises in their lifetime. These women were significantly more likely to be hospitalized compared with those who did not (mean 1.70 vs. 0.67, p = 0.0005). Women reporting menstruation-associated pain crises in the past 6 months also experienced increased hospitalizations compared with those who did not (mean 1.71 vs. 0.75, p = 0.0016). Forty percent of women reported at least four menstruation-associated pain crises in the past 6 months. Conclusions: Nearly 40% of SCD women have menstruation-associated pain crises. Menstruation-associated pain crises are associated with high pain burden and increased rates of hospitalization. Strategies are needed to address health care disparities within gynecologic care in SCD.
Research Article
Keywords: sickle cell disease; pain crises; menstruation; hospitalizations; health care utilization